Is It More Important to Address the Issue of Patient Mobility or to Guarantee Universal Health Coverage in Europe?; Comment on "Regional Incentives and Patient Cross-Border Mobility: Evidence From the Italian Experience" - Helena Legido-Quigley (Kerman University of Medical Sciences, 2016)
This paper discusses whether European institutions should devote so much attention and funding to cross-border healthcare or they should instead prioritise guaranteeing universal health coverage (UHC), inequalities and tackling the effects of austerity measures. The paper argues through providing the evidence in both areas of research, that the priority at European level from a public health and social justice perspective should be to guarantee UHC for all the population living in Europe and prioritise protective action for those who are most in need.